2013
DOI: 10.1002/wrcr.20232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seasonal variability and monitoring mode on the adequacy of fiber‐optic distributed temperature sensing at aquifer‐river interfaces

Abstract: [1] Fiber-optic distributed temperature sensing (FO-DTS) has been frequently applied for analyzing thermal patterns, including the identification of groundwater-surface water exchange fluxes across aquifer-river interfaces. However, the impacts of (a) seasonal variability in signal strength (given by the difference between groundwater and surface water temperatures) and (b) monitoring modes on the accuracy of FO-DTS surveys have not yet been determined. This study uses a well-investigated field site as model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
3
31
0
Order By: Relevance
“…6A, B) indicate a rapid dissipation of the colder ground water within the surface water column and coincide with previous findings by Krause et al (2012) and Krause and Blume (2013). These results suggest that FO-DTS provides a use- ful mean of identifying potential hotspots of groundwater seepage into proglacial lakes.…”
Section: Spatial Patterns Of Groundwater Dischargesupporting
confidence: 88%
See 1 more Smart Citation
“…6A, B) indicate a rapid dissipation of the colder ground water within the surface water column and coincide with previous findings by Krause et al (2012) and Krause and Blume (2013). These results suggest that FO-DTS provides a use- ful mean of identifying potential hotspots of groundwater seepage into proglacial lakes.…”
Section: Spatial Patterns Of Groundwater Dischargesupporting
confidence: 88%
“…We installed the buried cable by hand, and spot checks indicated that the deployment depth remained constant during the course of the experiment. The FO-DTS set-up used alternating single-ended measurements in clockwise and anticlockwise directions that we combined in 2-way single-ended averaging mode as described by Krause and Blume (2013). We did the dynamic temperature calibration in a calibration bath (containing meltwater from the river) where temperature was monitored continuously.…”
Section: Fo-dtsmentioning
confidence: 99%
“…The gained information is the spatial resolution, independent from the actual nature of the signal monitored outside the calibration system. While this might not be as important for applications with simpler temperature patterns such as step changes [e.g., Selker et al, 2006aSelker et al, , 2006bWesthoff et al, 2007], in systems with more complex, spatially heterogeneous temperature patterns including small-scaled thermal peaks [e.g., Lowry et al, 2007;Henderson et al, 2009;Krause et al, 2012;Krause and Blume, 2013] knowledge of the signal size impact on the detection of the actual signal intensity is crucial. This becomes even more important when interpreting temperature changes at small scale as for instance in surveys with coiled cable design [e.g., Vogt et al, 2010;Briggs et al, 2012a].…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Such shortfalls obviously impede a thorough assessment of the application specific capabilities and uncertainties of FO-DTS. With this in mind, the experiments of Rose et al [2013] were designed to complement recent benchmark studies on calibration strategies and sampling designs in single-ended [Hausner et al, 2011] and double-ended [ Van de Giesen et al, 2012] monitoring modes as well as investigations of the impact of single-ended and double-ended mode monitoring and combinations thereof, such as two-way single-ended averaging [Krause and Blume, 2013].…”
mentioning
confidence: 99%
“…The sensitivity of the method appeared to be relatively high since DTS was able to detect discharge of 2% of natural flow. Krause and Blume [123] determined the impacts of seasonal variability in signal strengths and monitoring modes on the accuracy of fiber-optic DTS systems used to analyze thermal patterns in aquifer-river interfaces. They found that the stability in signal strength was better in winter and that two-way single ended averaging surveys were the best suited for monitoring.…”
Section: Using Dts To Measure Temperaturementioning
confidence: 99%